The Development of Internalizing Behaviors in Early Adolescence: Introduction to the Special Issue. (November 2020) - Van Zalk, Nejra
This special issue highlights a number of important processes that help explain the emergence and continuation of internalizing psychopathology (i.e., problem behaviors characterized by inner distress) during early adolescence. The five articles making up the special issue are introduced, each of which represents exciting new work regarding how, why, and for whom internalizing problems develop and are maintained. The introduction to the special issue further elaborates on transdiagnostic and person-oriented approaches, internalizing interpretations and functional effects of internalizing as relatively underused methodological and theoretical perspectives that might help move the field forward and further our understanding regarding the development of internalizing psychopathology early on in life.